Towards a more sustainable architectural education in Malaysia - Shari, Zalina; Jaafar, Mohd Fakri Zaky (Faculty of Design & Architecture, Universiti Putra Malaysia, 2006)
The role of higher education in creating a more environmentally sustainable future is irrefutable. However, there is currently no clear evidence of definitive framework in training the professionals to be environmentally literate. The article is an extended analysis of a survey conducted to assess the level of integration and implementation of sustainability issues in the curricula of programmes at the schools of architecture in Malaysia. It looked on the level of awareness and training background of educators on sustainability and the sustainability content in studio projects and related courses. Based on the earlier findings, this article recommends the organisation of more training programs related to sustainability, the revision of existing curricula to inculcate sustainability awareness at lower years and the incorporation of humanistic aspects of sustainability into architectural education.